The Enhancement of Students’ Mathematical Conceptual Understanding Through RADEC Learning Model - Trisna Nugraha; Sufyani Prabawanto (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2021)
Students’ mathematical conceptual understanding (MCU) as major part of mathematical proficiency needs to be developed since elementary school through a didactic-pedagogical activity. One of these proficiency needs to be developed in the learning of perimeter and area of a plane geometry. The reason is students often find difficulties in understanding those concepts, especially in situations of distance learning due to COVID-19 pandemic. This study aims to investigate the achievement and enhancement of students’ MCU through RADEC learning model. This study used quasi-experimental method with non-equivalent pre-test and post-test control group design. Subjects of this research were 56 of 4th graders at one of private school in Bandung, Indonesia. This study found that there are significant differences in the achievement and enhancement of students’ MCU between students who received RADEC learning and direct learning where the RADEC learning model was higher in achieving & enhancing students’ MCU. In addition, the invention of the RADEC learning model on the achievement and enhancement of students’ MCU is in the moderate effect category with the acquisition of Hedges’ g of 0,922 in the level significant effect